Unofficial guide to FamilySearch.org : how to find your family history on the world's largest free genealogy website - McCullough, Dana (Family Tree Books, 2020)
"Discover your ancestry on FamilySearch.org, the world's largest free genealogy website. This in-depth user guide shows you how to find your family in the site's databases of more than 3.5 billion names and millions of digitized historical records spanning the globe. Learn how to maximize all of FamilySearch.org's research tools--including hard-to-find features--to extend your family tree in America and the old country." -- Back cover.